1985
DOI: 10.1093/carcin/6.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variations in the activities of cytosolic and microsomal epoxide hydrolase in human liver

Abstract: Mammals have at least two epoxide hydrolases (EHs) with a broad significance in drug metabolism. One enzyme is localized in the endoplasmic reticulum and other membranes (EHm), and the other is in the cytosol (EHc). In the present study we found that humans differ greatly in the activities of these enzymes in liver. The specific activities in microsomes from 166 subjects (most of them patients suffering from hepatic diseases), measured with benzo[a]pyrene 4,5-oxide as the substrate, varied by a factor of 63. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…mEH activity ex vivo exhibits a relatively large interindividual variation, [16][17][18][19] which might be explained, at least in part, by differences in mEH gene sequences. Genotype/ phenotype correlations, however, are imperfect, indicating an effect of induction/inhibition of enzyme expression possibly because of posttranscriptional/posttranslational mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mEH activity ex vivo exhibits a relatively large interindividual variation, [16][17][18][19] which might be explained, at least in part, by differences in mEH gene sequences. Genotype/ phenotype correlations, however, are imperfect, indicating an effect of induction/inhibition of enzyme expression possibly because of posttranscriptional/posttranslational mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…15 Microsomal epoxide hydrolase (mEH) is expressed in all tissues, with the highest levels in liver, kidney, and testis, 13,16 and it is primarily involved in the metabolism of xenobiotics with a wide substrate specificity. There is evidence for polymorphic mEH expression in humans, [16][17][18][19] and allelic variants of mEH have been identified. 20,21 Two point mutations in the coding sequence lead to amino acid changes, Tyr113His and His139Arg, which affect mEH activity by influencing protein stability.…”
mentioning
confidence: 99%
“…Tissues have developed the capacity to metabolize xenobiotic epoxides through several pathways. Prominent among these is the microsomal epoxide hydrolase (EPHX) 1 pathway.A wide variation of interindividual EPHX1 activities have been reported across human tissues (Mertes et al, 1985;Omiecinski et al, 1993;Hassett et al, 1997). We previously characterized two structural polymorphisms, an exon 3 polymorphism corresponding to amino acid position 113, with a resulting Tyr to His substitution (rs1051740), and an exon 4 polymorphism at position 139, coding for a His-to-Arg sub- …”
mentioning
confidence: 99%
“…A previous study found high interindividual variation in hsEH activity [e.g., more than 500-fold in liver (Mertes et al, 1985)], suggesting the existence of variation in coding or regulatory sequences of the gene. In addition, a study of human twins revealed a genetic component in hsEH enzymatic activity variation (Norris et al, 1989).…”
mentioning
confidence: 99%